Unemployment Benefits, Contract Length and Nominal Wage Flexibility - Lars Calmfors; Åsa Johansson (Center for Economic Studies and ifo Institute (CESifo), 2001)
We show in a union-bargaining model that a decrease in the unemployment benefit level increases not only equilibrium employment, but also nominal wage flexibility, and thus reduces employment variations in the case of nominal shocks. Long-term wage contracts lead to highter expected real wages and hence higher expected unemployment than short-term contracts. Therefore lower benefits reduce the expected utility gross of contract costs of a union member more with long-term than with short-term contracts and thus create an incentive for shorter contracts. Incentives for employers work in the same direction. Lower taxes associated with lower benefits also tend to make short-term contracts more attractive.
Keywords: 330; Nominal wage flexibility; contracts length; macroeconomic fluctuations; unemployment benefits